PROFILE OF THE POTENTIAL USER OF URBAN AIR MOBILITY IN THE CZECH REPUBLIC (Perner's Contacts, 2023)
Urban air mobility (UAM) is an emerging air transport concept in which drones transport passengers or cargo in densely populated areas. UAM enables significant reductions in travel times and bypasses traffic congestion by enabling air travel from one place to another within urbanized areas. However, before UAM can be implemented, several issues need to be resolved, including technical issues. Social acceptance and the creation of a viable business model are also important for the development of UAM. The survey described in this post aims to identify the profile of a potential UAM user. The results indicate a relatively high willingness to adopt UAM, with approximately 77% of respondents expressing interest, especially if the UAM journey would start from their area of residence. Logistic regression analysis revealed that gender, education, employment status, vehicle use patterns, air travel frequency, and motivational factors such as travel time use and travel speed significantly influenced the likelihood of UAM use. These findings contribute to the understanding of the potential user profile of UAM.
Keywords: urban air mobility (UAM); potential user profile; eVTOL